Please prove the inequalityProve that the inequality   (a+5b)(3a+2b)≥(a+9b)(2a+b) Holds real for all real numbers a and b. 

2 Answers | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to open the brackets both sides such that:

`(a+5b)(3a+2b)≥(a+9b)(2a+b)`

`3a^2 + 2ab + 15ab + 10b^2 >= 2a^2 + ab + 18ab + 9b^2`

Moving all terms to one side yields:

`3a^2 + 2ab + 15ab + 10b^2- 2a^2- ab- 18ab- 9b^2 >= 0`

Collecting like terms yields:

`a^2 - 2ab + b^2 >= 0`

Notice that if you expand the square `(a-b)^2`  yields `a^2 - 2ab + b^2` , hence, you may substitute `(a-b)^2 ` for `a^2 - 2ab + b^2`  such that:

`(a-b)^2 >= 0`

Notice that a square will always be positive, regardless the values of a and b and the square is zero if the values of a and b are equal, hence, the inequality `(a+5b)(3a+2b)≥(a+9b)(2a+b)`  holds for all real a and b.

bri-m's profile pic

bri-m | Student, Undergraduate | eNotes Newbie

Posted on

(a+5b)(3a+2b)≥(a+9b)(2a+b) , multiply out

3a^2 + 2ab + 15ab + 10b^2 ≥ 2a^2 + ab + 18ab + 9b^2 , add 'ab' terms together

3a^2 + 17ab + 10b^2 ≥ 2a^2 + 19ab + 9b^2 , algebraically move all variables to left side of inequality

a^2 - 2ab + b^2 ≥ 0 , factor

(a-b)(a-b) ≥ 0 , same as

(a-b)^2 ≥ 0 , any real number squared is positive or 0 (i.e. ≥ 0)

 

We’ve answered 318,956 questions. We can answer yours, too.

Ask a question